Tree cover and built-up area regulate the territory size in Eurasian Magpie Pica pica in Ladakh, India - Khan Iqbal Ali; Kumar Anil; Bhatt Dinesh; Rawal Prakhar (Wildlife Information Liaison Development Society, 2025)
Eurasian Magpie Pica pica is one of the well-studied corvids, but the majority of our understanding of this species is from Europe. In India, its distribution is restricted to some valleys of Ladakh such as the northwestern part of the Indus, Nubra, Zanskar, Drass, and Suru. The present study aimed at understanding the territorial behavior of this species in small urban settlements of Ladakh region. Twenty-five pairs were studied in March 2020–April 2021. Territories were outlined for each color-banded individual, and data on habitat variables (namely built-up, agriculture, and green cover) was extracted. Generalized linear mixed models were used to study the effect of the habitat structure on territory size. The territory size (Mean ± SD) was 0.042 ± 0.025 km2, with tree cover comprising the highest proportion (24.36 ± 15.41 %) of area within territories. Built-up area was a feature of all territories, highlighting the affinity of magpies towards human presence. Presence of tree cover and built-up area significantly (~ <0.002) reduced territory size. High adaptability, foraging, and nesting opportunities, and protection from predators have been recognized as the reasons for magpies’ affinity with human habitation. Foraging opportunities are minimal outside human settlements in this region, magpies’ territories are largely shaped by the fulfilment of foraging requirements.